2012
DOI: 10.3233/cbm-2012-0245
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional regulation of O6-methylguanine-DNA methyltransferase MGMT in glioblastomas

Abstract: Our results suggest mechanisms such as miRNA mediated regulation for post-transcriptional regulation of MGMT. Identification of these mechanisms should enhance the value of MGMT based prognostic or predictive biomarker strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…We, therefore, used this technique and also found that increased promoter methylation was associated with low MGMT protein expression, although it was not perfectly correlated at the individual level. This discrepancy is not entirely surprising, as numerous methylation-independent mechanisms of MGMT expression exist, such as miRNA, histone modifications, or NF-kB/STAT3-dependent regulation (Lavon et al 2007, Ramakrishnan et al 2011, Kitange et al 2012, Kohsaka et al 2012, Zhang et al 2012, Kreth et al 2013). In addition, comparative CpG arrays and transcriptomic arrays suggested that the CpGs tested in the pyrosequencing assay are not the ones most associated with MGMT mRNA expression (Bady et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, used this technique and also found that increased promoter methylation was associated with low MGMT protein expression, although it was not perfectly correlated at the individual level. This discrepancy is not entirely surprising, as numerous methylation-independent mechanisms of MGMT expression exist, such as miRNA, histone modifications, or NF-kB/STAT3-dependent regulation (Lavon et al 2007, Ramakrishnan et al 2011, Kitange et al 2012, Kohsaka et al 2012, Zhang et al 2012, Kreth et al 2013). In addition, comparative CpG arrays and transcriptomic arrays suggested that the CpGs tested in the pyrosequencing assay are not the ones most associated with MGMT mRNA expression (Bady et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This finding also signaled the limitation of MGMT promoter methylation assay, as one should not use an unmethylated result to preclude the use of TMZ in GBM patients because other MGMT silencing mechanisms could occur and patients might still benefit from this treatment. Recent studies concerning post-transcriptional regulation of MGMT have demonstrated that it could be regulated by miRNA via direct and indirect regulations [35][36][37]. Several miRNAsmiR181d, miR767-3p, miR-648 and miR-603 have been identified as significant post-transcriptional regulators of MGMT in GBMs [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that decreased MGMT expression may be related not only to promoter methylation, but also to the methylation of other promoter-associated CpG islands [37]. Potential binding sites for several miRNAs within the 3 0 UTR of MGMT have been found [38], indicating that mechanisms such as miRNA might mediate the post-transcriptional regulation of MGMT. The identification of these regulatory mechanisms will be beneficial for MGMT-based prognostic or predictive biomarker strategies.…”
Section: Regulation Of Mgmt Expressionmentioning
confidence: 98%